Ответы и объяснения

2013-06-17T12:24:05+00:00

1) 2KOH + H2SO4 = K2SO4 + 2H2O

2K(+) + 2OH(-) + 2H(+) + SO4(2-) = 2K(+) + SO4(2-) + 2H2O

OH(-) + H(+) = H2O

2) Fe2O3 + 6HCl = 2FeCl3 + 3H2O

Fe2O3 + 6H(+) + 6Cl(-) = 2Fe(+) + 6Cl(-) + 3H2O

Fe2O3 + H(+) = Fe(+) + H2O

3) 2AgNO3 + CaCl2 = 2AgCl + Ca(NO3)2

 2Ag(+) + 2NO3(-) + Ca(2+) + 2Cl(-) = 2AgCl + Ca(2+) + 2NO3(-2)

 Ag(+)  + Cl(-) = AgCl 

4) Na2CO3 + 2HNO3 = 2NaNO3 + H2CO3

 Na(+2) + CO3(2-) + 2H(+) + NO3(-) = 2Na(+) + NO3(-) + H2CO3 

H(+) + CO3(2-) = H2CO3